Adherence to the enhanced recovery after surgery protocol and its influencing factors among patients in Southwestern China: a multicenter cross-sectional study - Mu, Tong; Chen, Yuanhang; Ren, Li; Lv, Feng; Hu, Jingjie; Liu, Chunyuan; Wang, Chaofeng; An, Ran; Shen, Yiwei (Frontiers in Medicine, 2025)
BackgroundThere is limited research on adherence to Enhanced Recovery After Surgery (ERAS) protocols among hospitalized patients and the factors influencing it, both in China and globally.MethodsA random sample of 1,203 participants from 45 hospitals in Southwestern China was surveyed on ERAS protocol implementation, including 16 items. A questionnaire assessed awareness, attitudes, and social and environmental support factors. Multivariable linear regression model was used to analyze factors affecting ERAS adherence.ResultsThe final analysis included 806 surgical patients, with an average ERAS adherence rate of 71.5% (56.3, 81.3%). The highest completion rates were seen in avoidance of prolonged fasting (88.6%) and prophylactic antibiotic use (88.2%), while the lowest were in preoperative oral carbohydrate intake (42.2%) and deep vein thrombosis prevention (52.4%). Factors positively influencing adherence included educational background (p = 0.010), surgical grade (p = 0.013), positive attitudes toward ERAS (p < 0.001), perception of ERAS (p < 0.001) and social and environmental supports (p < 0.001). Negative influences included non-tertiary center status (p = 0.039) and negative attitudes (p = 0.002).ConclusionERAS adherence in Southwestern China remains low, with various factors such as hospital grade, patients’ educational background, their perceptions and attitudes toward ERAS, and their social and environmental support influencing ERAS adherence rates.Clinical trial registrationhttp://clinicaltrials.gov, Identifier ChiCTR2400086759.